PENGEMBANGAN MODEL PERKULIAHAN BERBASIS MASALAH PADA MATA KULIAH MANAJEMEN PENDIDIKAN MELALUI SURVEI MANAJEMEN MADRASAH - ASMENDRI ASMENDRI (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2011)
This study aimed at describing students’ ability in finding solutions of the problems dealing with managerial problems found at Islamic schools as the conducted survey. Based on the data analysis and discussion, it was found that the students’ ability in finding solution was good. Students’ response toward the learning process of Manajemen Pendidikan (Educational Management) subject employing Islamic school management survey in general was effective because most of students gave positive responses.Kata kunci: pembelajaran berbasis masalah, manajemen pendidikan, dan survei manajemen madrasah